A note on invariant submanifolds of (k, μ)-contact manifolds - Avik De (Український математичний журнал, 2010)
The object of the present paper is to study invariant submanifolds of a (k, μ)-contact manifold and to find the necessary and sufficient conditions for an invariant submanifold of a (k, μ)-contact manifold to be totally geodesic.